ADMINISTRATIVE REGULATION IN RENDERING CIVIL SERVICE IN THE SYSTEM OF LEGAL ENACTMENTS - Valeria V. Lich (Статистика и экономика, 2016)
The article studies the place of administrative regulation in rendering civil service in the hierarchy of the Russian laws and regulations. The problem whether to consider administrative regulation in civil service as a departmental law, issued by federal authorities, or as a clarification to federal laws and an instruction on its execution, is discussed in the article.